PENGARUH KERAPATAN TANAMAN DAN KOMBINASI PUPUK NITROGEN ANORGANIK DAN NITROGEN KOMPOS TERHADAP PRODUKSI GANDUM - Yosefina Mangera (Universitas Musamus, Merauke, Papua, 2014)
The Research objective is to evaluate wheat growth by several plants density and combination of inorganic nitrogen and compost nitrogen. The research was conducted in Sirapu Village, SemanggaDistrict, at Merauke Regency and used Randomized Complete Block Design with 3 blocks replication. The first factor was plant density of three level, i.e., 25 cm x 10 cm, 25 cm x 15 cm, 25 cm x 20 cm.The second factor was combinationof inorganic nitrogen and compost nitrogenconsists of six levels, i.e., compost 0% + urea 0%, 0% compost + 100% urea, 25% compost +75% urea, 50% compost + 50% urea, 75% compost + 25% urea, 100%compost + 0%. This experiment resultshowedthatthere was nosignificant interactionbetweenthe densityandthe combination ofinorganicnitrogenand nitrogencompostforallcomponents of production ofthe wheat. In plant densityof 25 cmx 15cmora combinationof nitrogen inorganic and compost nitrogen of75% urea +25% compost, respectivelygivethe besteffectto support the productiongadum